Effects of Feeding Probiotics on the Localization of Cells Containing Immunoreactive Interleukin-6 in the Intestine of Broiler Chicks - Yukinori Yoshimura; Miwa Oda; Naoki Isobe (The Journal of Poultry Science, 2010)
The aim of this study was to examine whether treatments of chicks with probiotics affect the population of cells containing interleukin-6 (IL-6) and IgA in the intestine of broiler chicks. The diets with probiotics, Streptococcus faecalis, Clostridium buthricum, Bacillus mesentericus, were fed from day 0 to 10 of age. The sections of duodenum, pouch and tonsil region of cecum and colon were immunostained for IL-6 and IgA. The IL-6 immunoreaction products were identified in the leukocytes locating in the subepithelial tissues under the mucosal and crypt epithelium and lamina propria, and occationally in the the mucosal and crypt epithelium, in all birds. The density of immunoreactive (ir) IL-6 cell population in the mucosa tended to be lowest in the duodenum and highest in the colon. The density did not differ between control and probiotics groups on day 5; however, that in the cecum pouch and colon was significantly greater in the probiotics group than control on day 10. The IgA immunoreaction products were identified in the mucosal and crypt epithelial cells in all segments of the intestine, and some IgA-positive cells were localized in the lymphoid tissue in the cecum tonsil, whereas differences in their localization were not observed between probiotics and control groups. In conclusion, we suggest that probiotics increases the population of irIL-6 cells in the cecum and colon mucosal tissues of chicks. Because IL-6 is multifunctional cytokine for immune system, the increased IL-6 secretion may affect the immune functions in the intestinal mucosal tissues.